Cultural Intersection in the Novel "Kuli" by M.H. Szekely Luloofs - Sartika Sari; Umar Mukhtar Siregar; Hidayat Herman (ELT (English Language Teaching Prima Journal), 2025)
This article discusses the representation of cultural intersection in M.H. Szekely-Lulofs' novel Kuli, a colonial text that records the lives of indentured laborers on Deli plantations. Starting from the multi-ethnic historical context of North Sumatra, this research highlights how cross-ethnic encounters—Javanese, Sundanese, Madurese, Betawi, Malay, and even Chinese—are constructed through stereotypes, conflict, and power relations. Lulofs, a Dutch-descended female writer, uses her personal experiences in Deli as both the setting and the medium to depict a fragmented social reality. Utilizing the perspective of literary sociology, the analysis is directed towards two main aspects: first, ethnic diversity as the foundation of Deli society, shaped by migration and colonization; and second, intersectional conflicts arising as a consequence of differences in ethnic identities and representations within the narrative. The novel Kuli presents ethnic stereotypes in layers: Betawi people are depicted as arrogant, Madurese as tough, Sundanese as polite, and even Chinese who are socially and economically marginalized. This stereotype is not only an identity marker but also a source of conflict that culminates in intergroup violence. Inter-ethnic intersection is depicted ambiguously—on one hand, it gives rise to "ship brother" solidarity, while on the other, it triggers exclusion and criminalization. The novel Kuli, therefore, presents plurality as an arena of tension, where ethnic representations operate within a colonial framework that reinforces social hierarchies